Revisit Intention dalam Industri Modern: Analisis Pengaruh Kualitas Layanan, Produk, Suasana, dan Lokasi pada Restoran Berkonsep Santap Sepuasnya - Azizatusholihah, Salma; Paramitasari Syahlani, Suci (Universitas Muhammadiyah Surakarta, 2025)
The emergence of new players offering similar concepts has made competition between restaurants with an all-you-can-eat concept increasingly fierce. Companies need to maintain their business in the face of competition. The aim of this research is to analyze the influence of service quality, product quality, restaurant atmosphere and location on consumers' intention to visit again. Data collection was carried out by distributing questionnaires to 275 respondents online. Data analysis techniques consist of validity and reliability tests, classical assumption tests, descriptive statistical analysis, multiple linear regression analysis, and hypothesis testing using MS Excel, SmartPLS 4.0 and IBM SPSS 23 software. The research results show that service quality, product quality, The atmosphere of the restaurant and location simultaneously have a significant influence on consumers' intention to return to restaurants with an all-you-can-eat concept in the DKI Jakarta area. The variables product quality, restaurant atmosphere and location partially have a significant effect on consumers' intentions to return to restaurants with an all-you-can-eat concept in the DKI Jakarta area. However, the service quality variable does not partially influence consumers' intentions to return to restaurants with an all-you-caneat concept in DKI Jakarta.